Beschäftigung zwischen Mobilität und Stabilität: Empirische~Befunde und wirtschaftspolitische Folgerungen - Knut Gerlach; Olaf Hübler; Gesine Stephan (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2011)
– The objective of this paper is to present a short survey of our new research results to mobility and stability of employment on a micro level. This area of conflict is analyzed from an individual and a firm's perspective, taking institutional issues into account. More than previous studies, we investigate interactions between individual and firm side issues. The results can be assigned to four subsections. First, individual, firm and macroeconomic determinants of employment stability are identified. Second, the relevance of wages and job satisfaction for job changes is investigated. In addition to other findings, the results show for Germany that high job stability and high wages go hand in hand. There exist also unobserved determinants which operate as compensating wage differentials. Third, the impact of institutions on job mobility is analysed. The outcome demonstrates that employment in firms with a collective agreement is more stable than in other firms, while company level pacts are not very successful in stabilizing employment at least in the medium term. Fourth, the effects of wage subsidies on wages and employment duration are investigated. The analysis shows that subsidised workers stay significantly longer at their first employer than similar unsubsidised workers, while entry wages do not differ significantly between both groups.
Keywords: J28; J31; J62; J68; J5; 330; Arbeitskräftemobilität; zwischenbetriebliche Mobilität; labour turnover; Arbeitsplatzwechsel; Beschäftigungsdauer - Determinanten; Arbeitszufriedenheit; Lohnhöhe; Arbeitsplatzsicherheit; institutionelle Faktoren; Tarifbindung; Eingliederungszuschuss; Betriebszugehörigkeit; Öffnungsklausel; Wirtschaftspolitik; Bündnis für Arbeit